The Effect of Transport on Mortality and Morbidity in Preterm Infants Less than 32 Weeks of Gestation - Selahattin Katar; Doğan Yıldız; Abdülkadir Turgut; Mustafa Taşkesen; Günay Saka (Güncel Pediatri)
Introduction: The aim of this study was to compare mortality and morbidity rates of premature infants with gestational age of less than 32 weeks who were born in our hospital and those who were transported to our hospital after birth from other centers. Materials and Methods: Patients were divided into two groups; Group 1 included 40 patients who were born before gestational age of 32 weeks in our hospital, and Group 2 included 108 premature patients who were born before gestational age of 32 weeks in other centers and later transferred to our hospital. Morbidity and mortality rates were compared between the two groups (intraventricular hemorrhage (IVH), retinopathy of prematurity (ROP), respiratory distress syndrome (RDS), necrotizing enterocolitis (NEC), and bronchopulmonary dysplasia (BPD)). Results: Demographic characteristics, gender, body weight, and gestational age were similar in both groups (p>0.05). The rate of normal vaginal delivery births was higher in Group 2 (p<0.001). On admission, hypothermia was detected in 90% of the patients and hypoglycemia was found in 2.7% of patients in Group 2. Mortality was higher in Group 2 than in Group 1, however the difference was not significant (p>0.05). Although higher rates of IVH, ROP, RDS, NEC, and BPD were found in Group 2, there was no statistically significant difference between the two groups (p>0.05). Conclusions: Being transferred after birth has a negative effect on morbidity and mortality in premature infants. Thus, the best transport method is intrauterine transport except in state of an emergency, especially for infants with severe prematurity; these patients should be treated in centers with facilities of the highest level. (The Journal of Current Pediatrics 2014;1:16-9)